PRINSIP IRONI BAHASA MINANG - Yessy Prima Putri (Program Studi Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
The Minang language is the language used by the Minangkabau community, which has around 200 million speakers. Submission of intent in a speech in the Minang language is generally done using indirect speech, figures of speech, satire/irony, and parables. The Minang community can be said to have a polite and friendly culture in the Minang language known as the phrase